Leaders of the Pack Women and the Future of Veterinary Medicine - Smith, Donald F.; Kumble, Julie (Purdue University Press, 2017)
Veterinary medicine has undergone sweeping changes in the last few decades. Women now account for 55 percent of the active veterinarians in the field, and nearly 80 percent of veterinary students are women. However, average salaries have dropped as this shift has occurred, and even with women in the vast majority, only 25 percent of leadership roles are held by women. These trends point to gender-based inequality that veterinary medicine, a profession that tilts so heavily toward women, is struggling to address. How will the profession respond? What will this mean for our students and schools? What will it mean for our pets entrusted to veterinarian care? Who has succeeded in these situations? Who is taking action to lead change? What can we learn from them to lead the pack in our lives? Leaders of the Pack, by Julie Kumble and Dr. Donald Smith, explores key themes in leadership and highlights women in veterinary medicine whose stories embody those themes. In it, Kumble and Smith cull over three years of interviews to profile a wide variety of women as they share triumphs and challenges, lucky as well as tough breaks, and the sound advice and words that inspired them to take their careers in unanticipated directions. By sharing unique stories that illuminate different paths to leadership and reflecting on best practices through commentary and research, Leaders of the Pack will allow more female leaders to create wider pathways to the top of their profession.